MENGELOLA PAJAK UNTUK KESEJAHTERAAN ANGGOTA KOPERASI - Bambang - Widarno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2010)
ABSTRACT Tax assumed something that apprehend and avoided, though tax for the development of nation. On the other side co-operation is obliged to be secure and prosperous of its member. With the existence of tax of course prosperity obtained SHU is co-operation member will decreasing. At the time we attitude and manage obligation of taxation wisely, to be prosperity of member also form. In fact non impossible matter and contradictive that with execution obligation of taxation according to order, also can improve prosperity of member. Transformations some of earnings of service become deposit form prosperity of member (SKA) represent solution. Needed by socialization and support from meaning related parties will be important of management done tax wisely and is logical   Keywords: tax, earnings transformation, deposit prosperity of member.